STUDI PENGARUH PENDINGINAN OLI DENGAN SISTEM RADIATOR PADA SEPEDA MOTOR SUZUKI SHOGUN 110 CC - Irawan, Maschudi Ferry; Qiram, Ikhwanul; Rubiono, Gatut (Virtual of Mechanical Engineering Article, 2016)
Cooling  system  is  an  important  part  in  motorcycle.  Its  related  to  engine  performance. Radiatorcooling system can be applied in motorcycle. This research is aimed to get the effect of radiatoroil cooling system in Suzuki Shogun 110 c motorcycle.    The experiment that compare air cooling (standard system) with radiator cooling. Engine is running at1000, 1500, 2000 and 2500 rpm. Temperature measurement is done with K type thermocouple at 3 measurement points which are left side, right side and engine head. Measurement is done 3 times with 5 minutes interval using stopwatch. The result is used to get the  temperature average. The result shows that radiator oil cooling system has effect due to cooling performance. This system has better cooling performance than standard system.